Does central sensitization affect disease severity and spinal mobility in axial spondyloarthritis? - Janan Hosseinzadgan; Nazli Busra Cigercioglu; Yaşar Gül Baltaci (Hacettepe University Faculty of Health Sciences Journal, 2026)
Objectives: The aim of this study was to investigate the relationships between central sensitization and disease activity, functional status, and spinal mobility in individuals with axial spondyloarthritis, and to elucidate the role of central pain mechanisms in the clinical presentation.Materials and Methods: This cross-sectional observational study included 30 individuals aged 18–65 years diagnosed with axial spondyloarthritis. Disease activity was assessed using the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), functional status with the Bath Ankylosing Spondylitis Functional Index (BASFI), spinal mobility with the Bath Ankylosing Spondylitis Metrology Index (BASMI), central sensitization with the Central Sensitization Inventory (CSI), and pain catastrophizing with the Pain Catastrophizing Scale (PCS). Relationships between variables were analyzed using Spearman correlation analysis (p 0.05). Pain catastrophizing was not significantly associated with either clinical parameters or central sensitization.Conclusion: This study demonstrates that central sensitization in axial spondyloarthritis is particularly associated with functional limitation and spinal mobility, but may not parallel disease activity. These findings highlight the importance of considering central pain mechanisms beyond inflammatory indicators in disease assessment and emphasize the role of multidisciplinary, biopsychosocial-based rehabilitation approaches in clinical management.